Chemical changes of soil and litter properties of riparian and non-riparian zones in a tropical dry forest - Pessoa, Luiz Guilherme Medeiros; Miranda, Márcio Fléquisson Alves; Calheiros, Altanys Silva; Freire, Fernando José; Freire, Maria Betânia Galvão dos Santos; Barbosa, Mozart Duarte; Marangon, Luiz Carlos (Journal of Environmental Analysis and Progress, 2023)
Riparian zones of dry tropical forests are important due to their effect on nutrient cycling and carbon dynamics. It’s important to evaluate the changes that occur when these areas are altered, to ascertain the magnitude of nutrient gains or losses. This study compares soil and litter chemical changes in riparian and non-riparian zones. Plots were established for soil and litter sampling in riparian and non-riparian zones. Considering chemical analysis, litter, and soil surface sampling were performed at depths of 0.0 to 0.10 m and 0.10 to 0.20 m. The descriptive and principal component analysis assessed chemical attribute sets' soil and litter characteristics. We observed higher P, K, and Ca content at both depths in soils of the non-riparian zone. The total soil organic carbon content in the non-riparian zones was 1.28 and 1.51 times greater at 0-10 and 10-20 cm depths, respectively, than in the riparian zones. Additionally, the humic acid and humin fractions had strong correlations with soil nutrients and, thus, are responsible for maintaining fertility in riparian zones. Despite the chemical and organic inputs in the non-riparian zones, no significant differences were observed regarding the chemical properties of riparian areas as opposed to the soils of non-riparian areas due to the litter of the riparian zones being richer in nutrients.